"Saying no is no easy matter" A qualitative study of competing concerns in rationing decisions in general practice - Norheim Ole; Carlsen Benedicte (BMC, 2005)
Abstract Background The general practitioner in Norway is expected to ensure equity and effectiveness through fair rationing. At the same time, due to recent reforms of the Norwegian health care sector, both the role of economic incentives and patient autonomy have been strengthened. Studies indicate that modern general practitioners, both in Norway and in other countries are uncomfortable with the gatekeeper role, but there is little knowledge about how general practitioners experience rationing in practice. Methods Through focus group interviews with Norwegian general practitioners, we explore physicians' attitudes toward factors of influence on medical decision making and how rationing dilemmas are experienced in everyday practice. Results Four major concerns appeared in the group discussions: The obligation to ration health care, professional autonomy, patient autonomy, and competition. A central finding was that the physicians find rationing difficult because saying no in face to face relations often is felt uncomfortable and in conflict with other important objectives for the general practitioner. Conclusion It is important to understand the association between using economic incentives in the management of health care, increasing patient autonomy, and the willingness among physicians to contribute to efficient, fair and legitimate resource allocation.